2021
DOI: 10.1186/s12906-021-03363-6
|View full text |Cite
|
Sign up to set email alerts
|

A radiosensitizer, gallotannin-rich extract from Bouea macrophylla seeds, inhibits radiation-induced epithelial-mesenchymal transition in breast cancer cells

Abstract: Background Radioresistance can pose a significant obstacle to the effective treatment of breast cancers. Epithelial–mesenchymal transition (EMT) is a critical step in the acquisition of stem cell traits and radioresistance. Here, we investigated whether Maprang seed extract (MPSE), a gallotannin-rich extract of seed from Bouea macrophylla Griffith, could inhibit the radiation-induced EMT process and enhance the radiosensitivity of breast cancer cells. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…We have recently demonstrated that MPSE possessed promising anti-cancer activity and radiosensitization in breast cancer cells by inhibiting IR-induced pro-survival signaling [19]. This study extends this observation to HNSCC, where poor patient prognosis and treatment failure were found due to intrinsic tumor radioresistance in HNSCC.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We have recently demonstrated that MPSE possessed promising anti-cancer activity and radiosensitization in breast cancer cells by inhibiting IR-induced pro-survival signaling [19]. This study extends this observation to HNSCC, where poor patient prognosis and treatment failure were found due to intrinsic tumor radioresistance in HNSCC.…”
Section: Discussionsupporting
confidence: 71%
“…The reduced activation of STAT3 results in the downregulation of downstream target Bcl-XL and Mcl-1 and further induced apoptosis [18]. A notable recent report by our team showed that MPSE pretreatment before irradiation in breast cancer cells inhibits the radiation induced epithelial to mesenchymal transition (EMT) process and confers radiosensitivity, probably by attenuating the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) and mitogen-activated protein kinase (MAPK) pathways [19].…”
Section: Introductionmentioning
confidence: 99%
“…Before irradiation, pretreatment of MCF-7 with plum mango seed extract (MPSE) affected the chemoresistance (MCF-7/MPIR6). MCF-7/MPIR6 cells decreased Pgp (ABCB1) mRNA expression but still expressed MRP1 and BCRP mRNA similar to parent MCF7 [27]. This shows that pretreatment with MPSE is able to prevent drug resistance (chemoresistance) by reducing the expression of the ABCB1 gene associated with the drug efflux pump (P-gp).…”
Section: Anticancermentioning
confidence: 81%
“…This shows that the combination of MPSE therapy with IR can increase the radiosensitivity of breast cancer cells and increase radiation-induced DNA damage. This combination therapy also increases apoptosis higher than IR therapy alone [27]. MCF-7/FIR is breast cancer cells that survive after radiation, have potential as malignant cells characterized by a high migration rate compared to MCF-7 parent cells [24].…”
Section: Anticancermentioning
confidence: 99%
See 1 more Smart Citation